1990
DOI: 10.1111/j.1751-0813.1990.tb07383.x
|View full text |Cite
|
Sign up to set email alerts
|

Fertility indices for beef bulls*

Abstract: Young (16- to 30-month-old) beef bulls of 6 different genotypes were assessed for production and reproduction traits at different ages and intervals from single-sire mating. Fertility indices, in the form of multiple regression equations using pregnancy rate as the dependent variable, were derived from these assessments using non-orthogonal analyses of variance and covariance. "Among" and "within" genotype fertility indices showed significant correlations with pregnancy rate. "Within" genotype fertility indice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…2006) (Table 1). Perry et al. (1990a) reported that the best fertility indices, which included GnRH‐stimulated LH, were those assessed at 11, 8, 6 and 2 months prior to mating and were collectively significantly correlated with pregnancy rate (P < 0.01).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…2006) (Table 1). Perry et al. (1990a) reported that the best fertility indices, which included GnRH‐stimulated LH, were those assessed at 11, 8, 6 and 2 months prior to mating and were collectively significantly correlated with pregnancy rate (P < 0.01).…”
Section: Resultsmentioning
confidence: 96%
“…This test is simpler than multiple samplings as it requires an initial pre‐injection blood sample, followed by an injection of GnRH analogue, and a subsequent single 0.5 to 1 hourly blood sample. However, there are only a small number of publications describing the use of this test, and except for one study in bulls from 16–26 months of age (Perry et al. 1990a), most studies have only monitored the bulls to yearling age (Moura and Erickson 1997; Bagu et al.…”
Section: Resultsmentioning
confidence: 99%
“…Improvement in the percentage of progressively motile spermatozoa as the only abnormality observed could be explained by the influence of semen handling on sperm viability and the fact that this is a subjective assessment must not be overlooked [23]. The reliability of semen progressive motility assessment in relation to number of calves born per cow appears limited and requires further investigation [2], [24]. More accurate assessment of semen motility and morphology can be performed by the use of computer-aided semen assessment [23].…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, the serum testosterone level depends on the number of Leydig cells (maximal testosterone producing capacity of testis). Fertility indices, in the form of multiple regression equations using pregnancy rate as a dependent variable, were derived from production and reproduction traits of beef bulls in Perry's study (13). Fertility indices showed significant multiple correlation among and within genotype (P < 0.01) at 11, 8, and 6 months prior to mating, r=0.75, r=0.89, r=0.80, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The correlation values in this studiy support (Table 3) our previous results (18) in that there was a close correlation between the increased testosterone content in the serum and the testosterone level after GnRH treatment (Table l).This correlation may provide information about the responsiveness of Leydig-cells to LH. Perry et al (13) suggested that the most important traits in fertility are the peripheral LH levels after GnRH stimulation and the testicular volume. In our opinion, the serum testosterone level depends on the number of Leydig cells (maximal testosterone producing capacity of testis).…”
Section: Methodsmentioning
confidence: 99%